Wound breakdown reconstructed by reverse lateral arm flap after excision of heterotopic ossification of the elbow following severe burn injury: A case report. Issue 1 (July 2017) - Hirakawa, Akihiro; Ohno, Yoshiyuki; Komura, Shingo; Akiyama, Haruhiko
Abstract: We report the case of a wound complication that was reconstructed by reverse lateral arm flap after excision of heterotopic ossification (HO) of the elbow in a patient with severe burns. Careful attention should be paid to wound complication and HO recurrence in patients undergoing surgical treatment for elbow HO following burn injury.